A microchemical analysis of acid values in stored wheat. Issue 4 (14th March 2022) - Li, Ping; Yang, Wei; Cong, Fangdi; Zhang, Ailin; Zhang, Shulin; Wang, Yingchao; Su, Yongpeng; Liu, Daying; Liu, Haixue; Li, Tao
Abstract: Background and Objectives: Quantifying the acid value of stored wheat is of great significance for timely treatment and avoiding waste. For the low‐fat content in wheat, the aim of this study is to propose a microchemical way for the acid value analysis. Findings: Twenty‐four wheat samples are taken from the grain reserve depot and the acid values of them are analyzed by the spectral response of one phthalocyanine dye, tetra‐ α ‐octoxy substituted zinc phthalocyanine, to a fatty acid. Under the experimental conditions, a linear relation exists between the absorbance of this dye at 749 nm ( A 749 nm ) and the concentration logarithm (ln c b ) of fatty acid (palmitic acid) in chloroform, R 2  = 1.000. Conclusions: By the aforesaid linearity, 1 µl of extracted wheat oil is enough to determine the acid values of wheat samples, which can avoid the interference from the color of the sample in traditional titration. Significance and Novelty: The UV‐visible method has great potential in the actual analysis of the acid value of wheat samples and has important reference value for the analysis of other related agricultural products, food and drugs, and so on.